Energy system development in elite mixed martial arts - Harvey, B. N. (Journal of Australian Strength and Conditioning, 2018)
High intensity intermittent efforts are an important determinant of match winning performances in the sport of mixed martial arts (MMA). Given the majority of MMA contests end in decision, the development of these energy systems (lactic/alactic) is vital to success. Using online and hard copy journals from 1985-present (53 studies included) this paper reviewed methods of energy system development (ESD) in MMA and its associated combat sports (JUDO, Muay Thai, Boxing, Wrestling, Taekwondo) to provide evidence-based recommendations for coaches to apply in their respective fields. MMA athletes during competition average a 1:2-1:4 work to rest (W:R) ratio, yet can be further categorised into grappling (1:1 W:R ~30s at max intensity) or striking dominant fighters (1:3-4 W:R ~10s at max intensity), thus demonstrating the importance of anaerobic metabolism and an individualised approach to ESD. With high technical/tactical training loads, MMA athletes require time effective ESD. High intensity intermittent training (HIIT) is a time effective modality that can be easily manipulated (W:R ratios, intensity and specificity) to address the metabolic requirements of individual MMA athletes. HIIT can be applied using 3 key methods; circuit training, MMA specific interval training or non-specific interval training. These can be programmed as stand-alone and/or integrated training sessions, thus saving time, and developing skill and tactical awareness under stress. Although there is no substitute to the sport specific training of MMA, emphasizing the aforementioned methods of ESD over competitive free-sparring provides a reduced injury risk and a measurable stimulus to be tracked and manipulated. This may prove a safer and more effective way of inducing metabolic adaptations to enhance physical fitness and thus leaving free-sparring to be utilised for tactical/technical development.